Ear Voice Span in English into Korean Simultaneous Interpretation - Lee, Tae-Hyung (Meta, 2002)
AbstractA computer-aided analysis of some 800 sentences taken from English into Korean simultaneous interpretation(SI) revealed that the average ear-voice-span (EVS) is 3 seconds. Statistical analysis showed that speaker variables, including the length of original English sentence, wpm, and pauses affected the length of EVS, and the EVS, in turn, affected the interpreter variables. When the EVS is lengthened, Korean interpreters increased the speed of their target language (TL) delivery to catch up with the speaker. Long EVS had a negative effect, not only on the quality of the sentence being processed, but also on the processing of the following sentence.